EFFECT OF HOST-LARVAL DIET ON THE HOST ACCEPTANCE AND HOST SUITABILITY OF THE EGG PARASITOID Telenomus remus NIXON (Hymenoptera: Scelionidae) ON Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae) - Sari, Adha; Buchori, Damayanti; Nurkomar, Ihsan (Universitas Lampung, 2021)
Effect of host-larval diet on the host acceptance and host suitability of the egg parasitoid Telenomus remus Nixon (Hymenoptera: Scelionidae) on Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae). The life history of parasitoids is an important factor that can determine their ability to attack a host. The type of food consumed by the host can affect the ability of parasitoids such as host searching behavior, host suitability and host acceptance. In this research, we evaluate the effect of the S. frugiperda larvae diet on its suitability of the eggs produced by the adults for the egg parasitoid Telenomus remus. The research was studied on two types of egg masses of S. frugiperda that obtained from the moths that fed with natural or artificial diet during their larval stages. Parasitoid was reared from both types of hosts. An egg mass consisting of 50 S. frugiperda eggs from both types of hosts was exposed to one egg parasitoid female for 24 hours. S. frugiperda eggs then were reared until the parasitoid adult emerged. Each experiment was repeated 20 times. Host acceptance was observed through the host parasitism rate and its parasitization. Meanwhile, the host suitability was observed through the sex ratio of the emerging parasitoids. The results showed that S. frugiperda eggs reared using artificial diet had a higher parasitism rate (99.33%) than those of natural diet (82.53%). In contrast, the level of parasitization of S. frugiperda eggs reared using natural diet was higher (78.30%) than those of artificial diet (48.34%) because the number of emerging T. remus from S. frugiperda eggs reared using natural diet was also higher than those of artificial diet. However, the sex ratio (F:M) of emerging T. remus from S. frugiperda eggs reared using both of diet was female biased.